Hypoglycemic Activity and Pancreas Protection of Combination Juice of Mengkudu (Morinda citrifolia Linn.) Juice and Temulawak (Curcuma xanthorrhiza Roxb.) Juice on Streptozotocin-Induced Diabetic Rats - Santoso, Bilal Subchan Agus; Sudarsono, Sudarsono; Nugroho, Agung Endro; Murti, Yosi Bayu (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2018)
Mengkudu fruit contains scopoletin and temulawak rhizome contains curcumin have been observed because they have strong antioxidant activity and they were used traditionally as antidiabetic. This research aimed to evaluate effect of antihyperglycemic and pancreas protection of juice combination of mengkudu fruit juice (MFJ) and temulawak rhizome juice (TRJ) on diabetes rats which were inducted with streptozotocin (STZ). Rats were grouped into 7 groups, each of group consisting 5 rats. Each of group was treated accordingly for 28 days except for a normal group of rats. Rats taken blood from the plexus retroorbitalis for examination of blood glucose levels every week. On the last day, rats blood was examined for malondialdehyde (MDA) levels. After that the rats were turned off for examination of pancreatic morphological conditions. The results showed that diabetic rats given MFJ-TRJ combination juice experienced a significant decrease in blood glucose levels, a significant decrease in MDA levels and improvement pancreas morphology when compared with the negative control group. The conclusion of this research was giving combination juice of MFJ-TRJ juice can decreased blood glucose level, decreased MDA level and can improved pancreas morphology condition.